Pengaruh Gaya Kepemimpinan dan Kepuasan Kerja Terhadap Kinerja Pegawai RSUD Dr hadrianus Sinaga Pangururan Kabupaten Samosir - Hutabarat, Yhourina (JEBIM Prima, 2023)
SUD Dr. Hadrianus Sinaga is a hospital that contributes to improving service and service quality in the Samosir Regency area with a population of 126,188 people. This research is quantitative research with a causal associative method, a sample of 75 people who are from RSUD Dr. Hadrianus Sinaga Panguruan in Samosir Regency. The results of this study simultaneously indicate that there is an influence of leadership style and job satisfaction on employee performance at RSUD Dr. Hadrianus Sinaga. Partially, the leadership style that is proxied by transformational leadership, transactional leadership, and Laisses Faire leadership can have a positive and significant effect on employee performance at Dr. Hadrianus Sinaga Hospital. Whereas job satisfaction stated the results partially had a negative and significant effect on employee performance at RSUD Dr. Hadrianus Sinaga.